The human multidrug-resistance-associated protein MRP1 mediates ATP-dependent transport of unconjugated bilirubin - Rigato, Igino (Portland Press Ltd., 2004)
Results of previous studies have suggested that UCB (unconjugated bilirubin) may be transported by MRP1/Mrp1 (multidrug-resistance-associated protein 1). To test this hypothesis directly, [(3)H]UCB transport was assessed in plasma-membrane vesicles from MDCKII cells (Madin–Darby canine kidney II cells) stably transfected with human MRP1 or MRP2; wild-type MDCKII cells served as controls. As revealed by Western blotting, transfection achieved abundant expression of MRP1 and MRP2. [(3)H]UCB uptake was measured in the presence of 60 μM human serum albumin at a free (unbound) concentration of UCB (B(F)) ranging from 5 to 72 nM and in the presence of 3 mM ATP or 3 mM AMP-PCP (adenosine 5′-[β,γ-methylene]triphosphate). MRP1-transfected vesicles showed transport activity three and five times higher respectively compared with MRP2 or wild-type vesicles, whose transport did not differ significantly. [(3)H]UCB transport was stimulated 4-fold by 1.5 mM GSH, occurred into an osmotically sensitive space, was inhibited by 3 μM MK571 and followed saturative kinetics with K(m)=10±3 nM (B(F)) and V(max)=100±13 pmol·min(−1)·(mg of protein)(−1). UCB significantly inhibited the transport of LTC4 (leukotriene C4), a leukotriene substrate known to have high affinity for MRP1. Collectively, these results prove directly that MRP1 mediates ATP-dependent cellular export of UCB and supports its role in protecting cells from bilirubin toxicity.